Monetary policy, interest rates and risk-taking - Mikael Apel; Carl Andreas Claussen (Sveriges Riksbank Economic Review, 2012)
The effects of monetary policy on the risks in the financial system are discussed intensively. One hypothesis that has attracted much attention is that monetary policy does not only act through the previously known channels, but also through a hitherto neglected channel – the risk-taking channel. According to this channel low policy rates lead banks and other financial institutions to take greater risks. In this article we conclude that there is international empirical support indicating that low interest rates result in greater risktaking, but also that there are several questions that need to be analysed further. One question is to what extent it is monetary policy or the general level of interest rates that is significant for the bank's risk-taking. The general level of interest rates – the neutral real interest rate – is not determined by monetary policy. Another question is to what extent a link between low interest rates and risk-taking is a sign that the banks are acting in a less responsible manner. It may well be optimal for a bank to increase its risk-taking when the interest rate is low. A third question is the role that the risk-taking channel played in the global financial crisis. If this crisis was partly due to individual banks taking excessively high risks – in the way that is implied by the risk-taking channel – the question arises why this was not detected by micro-prudential supervision.
Keywords: E52; E58; 330; Monetary policy; Risk taking channel